Adapting human thinking and moral reasoning in contemporary society - Yama, Hiroshi, 1959-; Salvano-Pardieu, Véronique, 1965- (Advances in religious and cultural studies (ARCS) book series., 2020)
"This book provides comprehensive research on thinking and morality and its influence on societal norms as well as how people adapt themselves to the novel circumstances and phenomena that characterize the contemporary world, including low birthrate, the reduction of violence, and globalization"--Provided by publisher.